MOBILE APPLICATIONS FOR PROMOTING AWARENESS OF CULTURAL HERITAGE AMONG RURAL COMMUNITIES: FEASIBILITY STUDY - Syifaun Nafisah; Nazrul Effendy (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society, 2025)
Rural communities in Indonesia are rich in intangible cultural heritage, including oral traditions, local languages, and indigenous knowledge. However, the transmission of this heritage to younger generations is increasingly threatened by modernisation, migration, and limited access to preservation tools. Mobile applications offer a promising avenue for bridging this gap by providing accessible, interactive platforms for cultural engagement. This study explores the potential of mobile applications to enhance cultural heritage awareness among rural communities in Indonesia. Specifically, it aims to identify key features and design elements that foster user engagement with cultural content. A qualitative exploratory design involved semi- structured interviews, app walkthroughs, and field observations in a rural Indonesian village. Thematic analysis was used to interpret the data and uncover patterns related to user experience and cultural interaction. Three major themes emerged: (1) cultural relevance and identity connection, where users felt pride and emotional resonance with culturally tailored content; (2) accessibility and digital literacy, highlighting generational divides and the importance of intuitive design; and (3) intergenerational engagement through interactive features, which fostered shared learning and strengthened family bonds. Mobile applications can serve as practical tools for cultural preservation when they are culturally responsive, accessible, and designed to support intergenerational interaction. The study contributes to the growing discourse on digital heritage and offers practical insights for designing mobile technologies that empower rural communities to sustain and celebrate their cultural identities.